Opportunities and challenges in applying reinforcement learning to robotic manipulation: An industrial case study - Toner, Tyler; Saez, Miguel; Tilbury, Dawn M.; Barton, Kira (Manufacturing letters, 2023)
As manufacturing moves towards a more agile paradigm, industrial robots are expected to perform more complex tasks in less structured environments, complicating the use of traditional automation techniques and leading to growing interest in data-driven methods, like reinforcement learning (RL). In this work, we explore the process of applying RL to enable automation of a challenging industrial manipulation task. We focus on wire harness installation as a motivating example, which presents challenges for traditional automation due to the nonlinear dynamics of the deformable harness. A physical system was developed involving a three-terminal harness manipulated by a 6-DOF UR5 robot, with control enabled through a ROS interface. Modifications were made to the harness to enable simplified grasping and marker-based visual tracking. We detail the development of an RL formulation of the problem, subject to practical constraints on control and sensing motivated by the physical system. We develop a simulator and a basic scripted policy with which to safely generate a data-set of high-quality behaviors, then apply a state-of-the-art model-free offline RL algorithm, TD3 + BC, to learn a policy to serve as a safe starting point on the physical system. Despite extensive tuning, we find that the algorithm fails to achieve acceptable performance. We propose three failure modalities to explain the learning performance, related to control frequency, task symmetry arising from problem simplifications, and unexpected policy complexity, and discuss opportunities for future applications.